Subfamilial affiliation of Neoscirula (Acari : Prostigmata : Cunaxidae) and descriptions of three new species of this genus from Brazil - Den Heyer, Jacob; Martins Gomes de Castro, Tatiane Marie [UNESP] (Magnolia Press, 2008)
The original affiliation of the genus Neoscirula Den Heyer to the subfamily Coleoscirinae Den Heyer, 1979 is maintained. Three new species of this genus are described and illustrated, viz. N. flechtmanni sp. nov., N. oliveirai sp. nov. and N. queirozi sp. nov.. A key to the Brazilian and South African species is provided.
Keywords: Bdelloidea; coleoscirinae; Neotropical; Taxonomy; identification key